Grupo de aquicultura da Unesp-Dracena: GAUD (2014-2015) - Ribeiro Junior, Ubiracy Lopes [UNESP]; Oshiro, Amanda Miyuki [UNESP]; Silva, Thais Daltoso da [UNESP]; Longhitano, Gabriela Cristina [UNESP]; Santos, Guilherme Lima dos [UNESP]; Andrade, Mikaely Larissa Dias [UNESP]; Sousa, Luana Camargo [UNESP]; Takahashi, Jaqueline Dalbello Biller [UNESP]; Miasaki, Celso Tadao [UNESP]; Takahashi, Leonardo Susumu [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Aquaculture is one of the fastest-growing agricultural activity, receiving great interest and space in the world market. The development of technologies that improve the productive system and meet the demand of the market, has increasingly made the activity search for qualified professionals for that function. The Grupo de Aquicultura da Unesp - Dracena (GAUD) aims at the technical and human development of those involved, seeking the dissemination of knowledge coupled with meeting the demands of society. During the period between February 2014 and July 2015, the group has developed several academic activities, such as technical visits to fish farms and companies, participated in the organization of events, in addition to the weekly meetings, allowing goals to be achieved.

A aquicultura é uma das atividade agropecuárias que mais cresce a cada ano, despertando grande interesse e espaço no mercado mundial. O desenvolvimento de tecnologias que aprimorem o sistema produtivo e atendam as demandam do mercado de trabalho, tem cada vez mais feito a atividade buscar por profissionais qualificados para tal função. O Grupo de Aquicultura da Unesp - Dracena (GAUD) tem como objetivo o desenvolvimento técnico e humano dos envolvidos, buscando a difusão do conhecimento aliado ao atendimento das demandas da sociedade. Durante o período entre fevereiro de 2014 e julho de 2015, o grupo desenvolveu diversas atividades acadêmicas, como visitas técnicas a pisciculturas e empresas, participou da realização de eventos, além das reuniões semanais, permitindo que os objetivos fossem alcançados.
Keywords: Aquaculture; Rural development; Difusion; Aquicultura; Desenvolvimento rural; Difusão